Promoting sustainable dairy production amid climate change: adoption of climate-smart dairy strategies and welfare effects on farmers in Central Kenya - Chelang'a, Naomi Chebiwot; Mathenge, Mary; Otieno, Dickson Okello; Sassi, Maria (Frontiers in Sustainable Food Systems, 2025)
IntroductionIn Kenya, smallholder dairy farming is a livelihood and a cornerstone of the national economy, accounting for 80% of the country's milk supply and a significant portion of its GDP. Yet, this sector grapples with sustainability challenges, marked by high methane emissions and a downturn in milk yields. To combat these issues, climate-smart dairy strategies, including improved breeding, feeds and feeding, animal health management, manure management, and zero grazing, are being championed. These strategies aim to boost production sustainably, fortify resilience against climate variability, and curtail emissions. Despite their potential, the uptake of these strategies is sporadic and uneven. This study delves into the effects of climate-smart dairy strategies on milk productivity and gross margins in Kenya.MethodologyThis study employed a multinomial endogenous switching regression model on 385 respondents in Nyandarua County. The data sheds light on the determinants of adopting climate-smart dairy strategies and their effects on milk productivity and gross margin.Results and discussionAccording to the findings, age, education, cooperative membership, group duration, entrepreneurial orientation, distance to input market, and risk perception significantly influenced the uptake of climate-smart dairy strategies. Further, the adoption of improved breeding, improved feeds and feeding, and animal health management significantly increased milk productivity (ATT = 547 litres) and gross margin (ATT = KES 18649) for adopters, indicating that adopting multiple strategies is effective. The study offers robust support for implementing holistic and cohesive climate-smart dairy strategies. These strategies are pivotal in optimising productivity and enhancing the dairy sector's economic viability. The study underscores the need for targeted policies to improve the adoption of sustainable dairy practices, offering comprehensive insights into balancing economic and environmental goals in smallholder dairy farming.